The Nrf2/HO-1 signaling pathway in arthritis: from molecular mechanisms to therapeutic potential - Zhang, Lin; Huang, Xianpeng; Xiong, Huazhang; Yang, Lidan (Frontiers in Cell and Developmental Biology, 2026)
Arthritis, a group of common diseases characterized by joint inflammation, cartilage destruction, and imbalance in bone remodeling, has high global prevalence and disability rates. In recent years, oxidative stress and chronic inflammation have been widely recognized as core mechanisms jointly driving its pathological process. The antioxidant response axis formed by nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) plays a key role in maintaining joint tissue redox balance and suppressing excessive inflammatory responses. Extensive basic and translational research indicates that the Nrf2/HO-1 pathway exerts protective effects through multiple mechanisms: reducing reactive oxygen species (ROS) levels, inhibiting nuclear factor-kappa B (NF-κB)-mediated inflammation, regulating macrophage polarization, and influencing processes such as apoptosis, ferroptosis, and fibrosis, thereby significantly alleviating tissue damage and clinical symptoms in arthritis. Currently, various natural products, small-molecule compounds, and drug repurposing strategies targeting the activation or regulation of this pathway have shown promising joint protective effects in animal experiments, suggesting Nrf2/HO-1 is a potential disease-modifying therapeutic target. This review systematically summarizes the latest research progress on the role of Nrf2/HO-1 in the pathogenesis of arthritis, experimental evidence from cellular and animal models, therapeutic strategies targeting this pathway, and discusses key scientific and technical challenges for future clinical translation.